Acute Toxicity of Ethanolic Extract of Leucaena leucocephala (Lam) de Wit Seeds in Wistar Rats - Fanany, Irzal; Nainggolan, Marline; Y, Yuandani; Husein, Saddam (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: This study was conducted to investigate the toxic effect of ethanol extract of Leucaena leucocephala(Lam) de Wit seeds(EELLS) in rats. Method: simplicia powder of L.leucochepala seeds extracted by maceration with 80% of ethanol. Evaluation of toxicity effect used the fixed dose method which refer to OECD (Organization of Economic Cooperation and Development)420. Result: Acute toxicity evaluation in this experiment using different doses varying from 50-2000mg/kgbw, did not result in the death of any animals until 14 days of observation in the experimental evaluation period and there was no change in behavior towards rats. Conclusion: These results have shown that oral administration of L. leuceocephala did not produce any significant toxic effect in rats. Hence, L. leucocephala could be regarded as a safe natural product for therapeutic use